The Role of Career Development as a Mediator in the Relationship Between Emotional Intelligence, Work Engagement, and Work Motivation and the Performance of Generation Z Employees at PT. Asuransi Sinar Mas - Wahyu Baswara Seta, D.; Karambut, Fermico; Haryanti, Enny; Sulistyowati (Journal Research of Social Science, Economics, and Management, 2026)
The increasing presence of Generation Z in the workforce has created new challenges for organizations, particularly in managing employee performance through approaches that align with their characteristics, such as self-development orientation, career expectations, and meaningful work experiences. In the insurance industry, employee performance is a critical factor in maintaining competitiveness; however, psychological factors such as emotional intelligence, work engagement, and work motivation may not always directly improve performance without adequate organizational support. This study aims to examine the role of career development as a mediating variable in the relationship between emotional intelligence, work engagement, work motivation, and the performance of Generation Z employees at PT Asuransi Sinar Mas. This research employed a quantitative explanatory approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through questionnaires distributed to Generation Z employees selected using purposive sampling based on specific criteria. The findings indicate that emotional intelligence, work engagement, and work motivation do not have a direct significant effect on employee performance. However, these three factors have a positive and significant effect on career development, while career development significantly improves employee performance. Furthermore, career development was proven to function as a full mediating variable that bridges psychological factors and performance outcomes. The study concludes that organizations should strengthen structured career development systems through training, mentoring, and transparent career pathways to optimize Generation Z employee performance.